Identification of Immune-Related Therapeutically Relevant Biomarkers in Breast Cancer and Breast Cancer Stem Cells by Transcriptome-Wide Analysis: A Clinical Prospective Study - Wang, Linbang; Liu, Wei; Liu, Jingkun; Wang, Yuanyuan; Tai, Jiaojiao; Yin, Xuedong; Tan, Jinxiang (Frontiers in Oncology, 2021)
Cancer stem cells (CSCs) represent a subset of tumor cells that are responsible for recurrence and metastasis of tumors. These cells are resistant to radiotherapy and chemotherapy. Immunotherapeutic strategies that target CSCs specifically have provided initial results; however, the mechanism of action of these strategies is unclear. The data were requested from The Cancer Genome Atlas and Genotype-Tissue Expression, followed with the survival analysis and weighted gene co-expression network analysis to detect survival- and stemness-related genes. Patients were divided into three groups based on their immune status by applying ssGSEA with proven dependability by ESTIMATE analysis. The filtered key genes were analyzed using oncomine, GEPIA, HPA, qRT-PCR, and functional analysis. Patients in a group with a higher stemness and a lower immune infiltration showed a worse overall survival probability, stemness and immune infiltration characteristics of breast cancer progressed in a non-linear fashion. Thirteen key genes related to stemness and immunity were identified and the functional analysis indicated their crucial roles in cell proliferation and immune escape strategies. The qRT-PCR results showed that the expression of PIMREG and MTFR2 differed in different stages of patients. Our study revealed a promising potential for CSC-target immunotherapy in the early stage of cancer and a probable value for PIMREG and MTFR2 as biomarkers and targets for immunotherapy.